Antibiotic resistance of infectious agents associated with prior hospitalization - Daria Yu. Perfileva; Alexander G. Miroshnichenko; Evgeny S. Kulikov; Vyacheslav Yu. Perfilev; Vadim A. Boykov; Sofia V. Nesterovich (Belgorod National Research University, 2024)
Introduction: One of the frequent causes of re-hospitalization is infectious complications due to previous colonization of patient loci by microorganisms circulating in the hospital environment. In the conditions of real clinical practice among hospital-acquired infections (HAI), it is advisable to distinguish a special group of diseases - infections associated with previous hospitalization (IPAH). Of particular scientific interest is the study of the antibiotic resistance profile of IPAH pathogens in order to determine the further strategy of empirical antibiotic therapy. Materials and Methods: A two-center descriptive study was conducted in Tomsk region. We analyzed 170 cases of IPAH according to the medical records of patients receiving medical care in inpatient settings (form N 003/u) in the period from 2019 to 2023. Identification of microorganisms was carried out by classical bacteriological method. Results and Discussion: Gram-negative bacteria (95.3%) predominated in the etiology of pneumonia associated with prior hospitalization. Among Gram-negative microorganisms, the most frequent were K. pneumoniae, P. aeroginosa and K. oxytoca. Representatives of the families Enterobacteriaceae (48.2%), Staphylococcaceae (28.9%) and Enterococcaceae (10.8%) predominated in the etiology of surgical infection associated with previous hospitalization. In the species structure, the key pathogens were K. pneumoniae, S. aureus and E. coli. IPAH pathogens were characterized by an unfavorable resistance profile. Conclusion: Despite the fact that the etiological structure and antibiotic resistance profile of IPAH are similar to those of classical nosocomial infections, IPAH has important features that should certainly be taken into account when organizing medical care for this cohort of patients.